Adsorption of a Highly Toxic Aromatic Pollutant From Aqueous Solution Using Low Cost Activated Carbon: Equilibrium, Kinetic and Thermodynamic Aspects - Muhammad Hamayun (Science Faculty of Chiang Mai University, 2019)
Peanut husk (agricultural waste) was used as a precursor for the development of activated carbons by chemical activation with H3PO4 abbreviated as H3PO4-APHDC [Phosphoric acid Activated Peanut Husk Derived Carbon] and by physical activation with CO2 designated as CO2-APHDC [Carbon dioxide Activated Peanut Husk Derived Carbon]. Both H3PO4-APHDC and CO2-APHDC were found to have a high BET surface area of 1070.766 and 960.931 m2g-1. The prepared activated carbons were tested for the removal of a highly toxic aromatic compound (pyridine). Batch experiments were performed for the detoxification of notorious pyridine from aqueous solution as a function of various experimental parameters like effect of initial pH, contact time, initial concentration and temperature. Maximum adsorption of pyridine was observed in the pH range of 8-10 where 83.66% pyridine adsorption was observed at pH 9.0 by H3PO4-APHDC and 72.13% by CO2- APHDC. The rate limiting step in the adsorption kinetics data was interpreted by intraparticle and Boyd models which suggested film diffusion to be the rate controlling step. Langmuir isotherm model fitted well with the adsorption isotherm data. The adsorption capacities were found to increase with the increase in temperature indicating that adsorption is favorable at high temperature. Different thermodynamic parameters were evaluated which showed that the adsorption process was feasible, spontaneous and endothermic in nature.